Internalizing the Nation's Character Through Pancasila Education in Higher Education in the BANI Era - Lukmanul Hakim, Alif (Jurnal Polisci, 2024)
The development of the current era is so rapid that it has implications for the dynamics of life, which is also changing and developing rapidly. The development of this era must be based on a qualified capability to continue to exist in maintaining noble ideologies and values. Internalization of national character education to all generations of the nation must be carried out massively and comprehensively so that the meaning and purpose of strengthening this value becomes a reality, especially in the Brittle, Anxiety, Non-Linear, and Incomprehensive (BANI) era. This paper aims to describe the substance of the internalization of character education in Higher Education through the Pancasila Education course. The method in this paper is a literature study method that collects primary data from various literature sources related to character education, Pancasila, and the wetting substance of BANI. The results of this paper are (1) the internalization of Pancasila ideology, which is used as a national ideology, must be prioritized compared to studying other ideologies; (2) the actualization of the concept of Pancasila substance in everyday life, such as discipline, responsibility, tolerance, active, and intelligent, (3) Care for external developments based on the fundamental values of Pancasila. This paper concludes that Pancasila education is critical to be applied in higher education. However, it should be accompanied by improvements to convey its meaning and purpose properly and correctly.